The Russia-Ukraine conflict and global food security - Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
When Russia invaded Ukraine in February 2022, sparking fears of a global food crisis, IFPRI responded rapidly to the need for information and policy advice to address the crisis. From the first moments of the conflict, a new IFPRI blog series provided critical information and insights into the impacts on food security, caused by rising food, fertilizer, and fuel prices and trade disruptions, for vulnerable countries and regions. This book is a compilation of those blog posts, which include analysis of trade flows, tracking of food prices and policy responses, and results of impact modeling. Together, they provide an overview of how the crisis has progressed, how the international community and individual countries responded with efforts to ensure food security, and what we are learning about the best ways to ensure food security in the aftermath of a major shock to global food systems.